Immunotherapy for uveal melanoma. (June 2016) - Kim, Dae Won; Anderson, Jaime; Patel, Sapna P
Uveal melanoma (UM) is a rare cancer with a high mortality rate. In comparison to cutaneous melanoma, UM has unique immunological features. Arising in the immune suppressive environment of the eye, it maintains immune resistance once metastatic. This is considered a major obstacle for successful immunotherapy in UM. However, a growing body of evidence suggests strategies that may abrogate resistance and enhance antitumor immunity in UM. Recently, three new immune agents have been approved for melanoma. While these drugs demonstrate durable clinical responses with long-term remissions in metastatic cutaneous melanoma, only limited data exist in metastatic UM. In this review, immunological aspects of UM and data from clinical studies of immunotherapeutic agents and regimens for UM will be discussed.